Portable spectrometer-based cold stress detection in C3 and C4 plants - Maja Mazur; Vlatko Galić; Antun Jambrović; Aleksandra Sudarić; Tomislav Duvnjak; Maja Matoša-Kočar (Journal of Central European Agriculture, 2024)
Plant stress detection is crucial for enhancing crop yield, particularly in the face of climate change. Cold stress significantly affects photosynthetic activity and pigment composition in soybean (a C3 plant) and maize (a C4 plant), underscoring the need to identify stress signals before irreversible damage occurs. This study used portable spectrometers to non-destructively detect the early signs of cold stress-related processes in these crops. The spectral reflectance indices were measured to identify crop-specific stress responses. According to the results, pigment-based indices have better potential for crop-specific stress detection than general stress response indices. The normalized phaeophytinization index (NPQI) and normalized pigment chlorophyll index (NPCI) exhibited diverse responses in C4 maize compared to C3 soybean, indicating the potential for discerning stress-induced changes in chlorophyll and other pigment contents. The photochemical reflectance index (PRI), modified to specific wavelengths, emerged as a crucial tool for stress detection in both crops, showing strong correlations with photosynthetic parameters and biomass traits. Specifically, the strongest correlation was found between PRI(525, 570) and fresh mass in maize and PRI(555, 570) and fresh mass in soybean. This approach underscores the importance of advanced spectral techniques in understanding and improving crop responses to cold stress, highlighting their potential for precision agriculture.